ANALYSIS ACTIVITY 14C OF CORAL REEF IN KAYANGAN ISLAND - Nur Faiizah Firman; Alfian Noor; Muhammad Zakir; Maming Gaffar; Syafyuddin Yusuf (Marina Chimica Acta, 2018)
The work is to determine absorption capacity, optimum time analysis, efficiency enumeration (TDCR), specific activityof 14C and coral age. Steps taken are physical and chemical washing, CO2 absorption, and analysis using liquid scintillation counter Hidex 300 SL. Due to washing, the weight loss was 4.74%. Total carbon absorbed was 1,056 grams. CO2 absorption capacity using KOH was 47% while optimum time analysis by LSC was 30 minutes and average efficiency enumeration (TDCR) was 0.6877.  It was concluded that specific activityof 14C was 14.7361 DPM/gC and coral age in Kayangan Island was 310.49 years.